Competency-Based Human Resource Management In Improving Employee Performance At PT BPRS AL-Washliyah Medan City. North Sumatra Province - Mey Cindy; Hasrudy Tanjung (Jurnal Ekonomi, 2024)
Human resources are a very important factor in achieving company goals because human resources are one of the determining factors in whether a company is successful or not in achieving its goals. Therefore, performance management is very important for every company, because performance management is oriented towards managing the work implementation process and the results or work achievements of human resources. HR management consists of the words management and HR management. Management is the ability to manage the use of human resources and other resources effectively and efficiently. Competency is one of the most important factors for improving organizational performance and ensuring that the workforce provides a more accurate and precise perspective about employees and their work. variables - life balance, burnout, work culture, and job satisfaction in the organization